The knowledge of parents about frequency of body posture defects in early school age children - Makarczuk, Anna Krystyna (Journal of Education, Health and Sport, 2022)
The aim of the research was an attempt to assess the level of knowledge of parents of early school children about the frequency of posture defects. The research was conducted in 2017-2018 in five primary schools in Lodz. The method of diagnostic survey and analysis of documents were used. The study involved 521 parents of both genders. Data from 257 health cards were analyzed. The analysis of the obtained results indicates a low (unsatisfactory) level of parents' knowledge of the occurrence of posture defects in children.